Irisin Exerts Neuroprotective Effects on Cultured Neurons by Regulating Astrocytes - Kexin Wang; Hongyan Li; Hongxing Wang; Jun-hui Wang; Feng Song; Yu Sun (Mediators of Inflammation)
Neurons suffer detrimental effects from β-amyloid toxicity in Alzheimer’s disease. The exercise hormone, irisin, is found to induce a neuroprotective gene program and facilitates the beneficial effects on cognitive function. But no effort is made to test its direct protective effects on neurons against the Aβ-induced cell toxicity so far. In the present study, we investigated whether irisin could protect neurons against Aβ- (25–35) induced cell damage and explored the possible underlying mechanisms. Primary cell cultures of astrocytes and neurons were established. Conditioned medium from astrocyte was collected for the treatment and biochemistry assay study. To explore the protein expression changes, Western blot and ELISA assays were used in these in vitro cell culture models. Exposure of hippocampal neurons to 10 μM Aβ (25–35) caused significant reduction on cell viability, and the toxic effect was not significantly reduced by the coadministration of irisin. However, pretreated astrocyte-conditioned medium with irisin for 12 hours notably protected the neurons from the toxicity of Aβ. Also, we found that irisin could attenuate the release of IL-6 and IL-1β from cultured astrocytes and decrease the expression level of COX-2 and phosphorylation of AKT. Last, we found that irisin could reduce NFκB activation in astrocyte exposed to Aβ by preventing the phosphorylation and the loss of IκBα. Our finding may provide novel evidence for the future application of irisin in the treatment of Alzheimer’s disease and the memory dysfunction in diabetes mellitus.